Diversity and dynamics of microbial communities in brown planthopper at different developmental stages revealed by high‐throughput amplicon sequencing. (13th November 2019) - Wang, Zheng‐Liang; Wang, Tian‐Zhao; Zhu, Hang‐Feng; Pan, Hai‐Bo; Yu, Xiao‐Ping
Abstract: The microbiome associated with brown planthopper (BPH) plays an important role in mediating host health and fitness. Characterization of the microbial community and its structure is prerequisite for understanding the intricate symbiotic relationships between microbes and host insect. Here, we investigated the bacterial and fungal communities of BPH at different developmental stages using high‐throughput amplicon sequencing. Our results revealed that both the bacterial and fungal communities were diverse and dynamic during BPH development. The bacterial communities were generally richer than fungi in each developmental stage. At 97% similarly, 19 phyla and 278 genera of bacteria were annotated, while five fungal phyla comprising 80 genera were assigned. The highest species richness for the bacterial communities was detected in the nymphal stage. The taxonomic diversity of the fungal communities in female adults was generally at a relatively higher level when compared to other developmental stages. The most dominant phylum of bacteria and fungi at each developmental stage all belonged to Proteobacteria and Ascomycota, respectively. A significantly lower abundance of bacterial genus Acinetobacter was recorded in the egg stage when compared to other developmental stages, while the dominant fungal genus Wallemia was more abundant in the nymph and adult stages than in the egg stage. Additionally, the microbial composition differed between male and female adults, suggesting that the microbial communities in BPH were gender‐dependent. Overall, our study enriches our knowledge on the microbial communities associated with BPH and will provide clues to develop potential biocontrol techniques against this rice pest.